Reading Alterations in Parkinson's Disease Indicate Worse Cognitive Status. Issue 4 (14th February 2023) - Tsitsi, Panagiota; Nilsson, Mattias; Seimyr, Gustaf Öqvist; Larsson, Olof; Svenningsson, Per; Markaki, Ioanna
Abstract: Background: Reading difficulties are commonly reported in Parkinson's disease (PD). So far, only a few studies have assessed reading in PD, most of them confirming a different pattern in patients compared with healthy populations. Impaired oculomotor control is an early feature of PD. Cognitive deficits, on the other hand, may appear early, but they are most prominent at later stages. Although these two factors are thought to be responsible for the alterations in reading performance, it is unclear how each factor contributes to them. Objectives: To evaluate eye movements during reading in PD and healthy controls (HCs). Methods: Data from 42 HCs (36% men) and 48 patients with PD (67% men) at Hoehn and Yahr stages ≤3 were analyzed. PD participants were further divided into 2 groups based on their Montreal Cognitive Assessment (MoCA) score using a cutoff of ≥26. Eye movements were recorded with Tobii Pro Spectrum, a screen‐based eye tracker with a sampling rate of 1200 Hz. Results: PD participants performed fewer fixations per second ( P  = 0.033), with a longer mean ( P  = 0.037) and standard deviation fixation duration ( P  = 0.033) than HC, and further analysis showed that only patients with a lower MoCA score performed worse than HCs. Reading parameters were weakly associated with MoCA scores, irrespective of age and education. Conclusion: Changes in the reading pattern of PD patients are probably attributed to cognitive rather than pure oculomotor alterations.